Tempat sampah pintar berbasis sensor HC-SR04 menggunakan Aduino Uno R3 - Junaed, Ismail; Fauziah, F; Nuraini, Rini (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Humans can produce waste every day, both household waste and industrial waste which has various forms and types. Garbage can be a problem because it interferes with human health, causes unpleasant odors and air pollution. Awareness of disposing of waste in its place is currently considered very lacking. This is because trash cans in general still use a simple way, namely by opening and closing manually. In the design of this smart trash can it will facilitate the work of the cleaning agency. In this study, a smart trash can with HC-SR04 sensor was designed using Arduino Uno R3 With the HC-SR04 sensor, it can detect the distance of humans who want to throw away and detect garbage loads. The maximum and minimum distance from the sensor is 10-60 cm to open the lid of the trash can. Data processing uses Arduino Uno R3 with Atmega328p chip which functions as data processing and sending data. The testing process that is carried out periodically produces data in the form of differences in the original distance and the distance read by the sensor with a difference of 0-1 cm, while the minimum and maximum sensor distances are 10-60 cm. This system can also detect the garbage load if it is full and will send a notification in the form of SMS. Another benefit is to make people aware of the importance of health by disposing of waste in its place. The method used is the waterfall method to detect this object is the design method which consists of several stages, namely Requirements Analysis, Design, Circuit Implementation, Test Tools.